Outlier-Resistant Claim Reserving Using a Robust Chain Ladder Method with a 2.5 Interquartile Range Criterion - Naia Rafida Mumtaz; Jessica Sie; Sukono (Research Collaboration Community (RCC), 2026)
Claim reserving plays an essential role in evaluating outstanding liabilities in credit insurance portfolios, which are commonly characterized by irregular claim development patterns and the occurrence of extreme claim values. Such characteristics may influence the stability of reserve estimates when historical paid claim data exhibit high variability across development periods. Therefore, an appropriate reserving approach is required to accommodate these data features while maintaining a consistent estimation process. This study estimates claim reserves for a credit insurance portfolio using the Robust Chain Ladder method based on paid claim data. The analysis is conducted by constructing incremental and cumulative run-off triangles from historical claim payments. To address the presence of extreme observations, a residual-based outlier detection procedure is applied using an interquartile range criterion with a 2.5 multiplier. This approach aims to reduce the influence of extreme claim values while preserving plausible large claims inherent in credit insurance portfolios. The reserving process is performed iteratively until no further extreme observations are identified, resulting in an adjusted run-off triangle used for reserve estimation. Based on the adjusted run-off triangle, the total estimated claim reserve amounts to IDR 120,773,423,681. This value represents an actuarial estimate of outstanding claim liabilities across all accident periods derived from historical claim development under the applied reserving assumptions. The results provide an overview of reserve levels for credit insurance portfolios and illustrate the application of a robust reserving approach in the presence of irregular and volatile claim patterns.